The Anthropology of Sibling Relations
XII, 195 p. 7 illus.
Keywords: Drawing on international case studies, the contributors extrapolate a systematization of the ways in which siblingship is conceived on the basis of shared parentage, shared childhoods, and reciprocal care. They explore what makes these relations worth maintaining and how they contribute to community processes and to material and emotional survival.